Proposal of innovative approaches of relationship marketing in business - Lendel, Viliam; Varmus, Michal (Business: Theory and Practice, 2015)
The aim of this paper is to propose innovative approaches to relationship marketing that affect the process of building relationships with customers, based on a detailed analysis of the literary sources and the research. This proposal is supported by the information technology e-CRM and social CRM. The paper contains a detailed description of the procedure for successfully implementing innovative approaches to relationship marketing in business. This should serve mainly to marketing managers as a valuable tool in their use of innovative approaches to relationship marketing, especially in the process of obtaining innovative ideas from customers, in order to identify their needs and requirements. Furthermore, the paper contains the main results of our research aimed at identifying the extent of utilization of innovative approaches to relationship marketing in Slovak businesses. A total of 207 respondents were involved in the research (medium and large businesses and following methods were used: comparative method of qualitative evaluation method, the method of structured and structured interview method, observation, document analysis method (method of content analysis) and questionnaire method.